History and theory in Max Weber's 'Protestant Ethic'. (3rd April 2019) - Ghosh, Peter
ABSTRACT: It is an old cliché that Weber's 'Protestant Ethic' ( PE ) is historically wrong or deficient. Recent work by German sociologists has reinforced this view, with the aim of further demoting the text within Weber's oeuvre: as if it was a work of bad history and nothing more. This paper takes a contrary view. It argues that the text is neither 'wrong' (to say so is a category error) nor is it confined to the past. Rather, it is much misunderstood, and a principal reason for this is our ignorance of Weber's uniquely sophisticated historicism, an area of his thought that has hardly been examined hitherto. The PE must be read as a product of this historicism, and set within the comparative context of contemporary European historicism, which was then at its apogee. Seen in this light, it is not only a pre-eminent guide to Weber's modern social theory, but one of the most carefully constructed and original historical works in all of European thought.